Analisis Faktor Yang Berpengaruh Terhadap Ekspor Biodiesel Di Uni Eropa - Aziz Pradana; Kusmantoro Edy Sularso; Irene Kartika Eka Wijayanti (Pascasarjana Universitas Jenderal Soedirman, 2021)
Biodiesel is a substitute product for fossil oil or diesel which is made from vegetable oil. Indonesia as a producer of biodiesel which is made from palm oil. This derivative product of palm oil is supported by Government policies in its utilization and supply. This policy boosted the palm oil industry, so that production and export capacity increased for a decade. The European Union is the largest consumer of biodiesel. Therefore, Indonesia exports biodiesel to the European Union and has become one of the largest exporters in the region. The purpose of this study is to examine the factors that influence Indonesia's biodiesel exports in the European Union. The research method used is multiple linear regression analysis using OLS to examine the factors that affect the amount of Indonesian biodiesel exports in the European Union. The results show, the regression test of the factors that affect the amount of Indonesian biodiesel exports in the European Union, namely; EU biodiesel production and biodiesel consumption have a significant or positive effect on total exports of 0.54% and 0.14%; the factor of the Rupiah exchange rate against the Euro, Indonesian biodiesel consumption, the dummy anti-dumping duty policy, international biodiesel prices and Indonesian diesel consumption have negative effects - respectively -0.04%, - 0.63%; -71.7%; -0.27%; -0.04, while the CPO production factor and oil palm land area did not significantly affect the amount of biodiesel exports to the European Union. From these factors, the government needs to increase biodiesel production and maintain biodiesel consumption in the EU so that it does not decline. Increased bilateral diplomacy to partner countries in offering biodiesel needs to be increased so that Indonesian biodiesel has a very strong competitiveness and does not depend on just one trading partner.